PENGEMBANGAN KURIKULUM PRACTICAL LIFE DALAM MENINGKATKAN KECERDASAN EMOSIONAL SISWA KELAS 1 MADRASAH IBTIDAIYAH MUMTAZA ISLAMIC SCHOOL - Rasmin, Rumiyati S. Dipl Montessori; Zulfitria, Zulfitria (Penerbit Widina, Widina Media Utama, 2025)
Emotional intelligence is an essential factor influencing students’ success in both learning and social life. This study aims to develop a Practical Life Curriculum to enhance the emotional intelligence of first-grade students at MI Mumtaza. The research employed a Research and Development (RD) approach using the ADDIE model, consisting of the stages of analysis, design, development, implementation, and evaluation. Participants included 25 first-grade students, two classroom teachers, and two experts in child education and curriculum development who served as validators. Research instruments comprised validation sheets, teacher observation sheets, and an emotional intelligence test based on Goleman’s five aspects: self-awareness, self-regulation, motivation, empathy, and social skills. Data were analyzed using descriptive quantitative and qualitative techniques. The results revealed that the Practical Life Curriculum was categorized as highly feasible with an average expert validation score of 89%. The practicality aspect reached 87%, and its effectiveness was indicated by the improvement in students’ emotional intelligence with an n-gain value of 0.67 (moderate-high category). These findings demonstrate that Practical Life activities—such as arranging desks, folding clothes, brushing teeth, and caring for the environment—foster independence, responsibility, and social awareness. Thus, the Practical Life Curriculum based on the ADDIE model is proven effective in enhancing the emotional intelligence of students in Islamic-based primary education.ABSTRAKKecerdasan emosional merupakan aspek penting yang berpengaruh terhadap keberhasilan siswa, baik dalam belajar maupun dalam kehidupan sosial. Penelitian ini bertujuan mengembangkan Kurikulum Practical Life sebagai upaya meningkatkan kecerdasan emosional siswa kelas I MI Mumtaza. Penelitian menggunakan pendekatan Research and Development (RD) dengan model ADDIE yang meliputi tahap analisis, perancangan, pengembangan, implementasi, dan evaluasi. Subjek penelitian terdiri atas 25 siswa kelas I, dua guru wali kelas, serta dua pakar pendidikan anak dan kurikulum sebagai validator. Instrumen penelitian meliputi lembar validasi, lembar observasi guru, dan tes kecerdasan emosional berdasarkan lima aspek Goleman, yaitu kesadaran diri, pengaturan diri, motivasi, empati, dan keterampilan sosial. Analisis data dilakukan dengan teknik deskriptif kuantitatif dan kualitatif. Hasil penelitian menunjukkan bahwa Kurikulum Practical Life memperoleh kategori sangat layak dengan rata-rata skor validasi ahli sebesar 89%. Aspek kepraktisan mencapai 87%, sedangkan efektivitas pembelajaran terlihat dari peningkatan skor kecerdasan emosional siswa dengan nilai n-gain sebesar 0,67 (kategori sedang-tinggi). Temuan ini membuktikan bahwa aktivitas Practical Life seperti menata meja, melipat pakaian, menyikat gigi, dan merawat lingkungan mampu menumbuhkan kemandirian, tanggung jawab, dan kepedulian sosial siswa. Dengan demikian, kurikulum Practical Life berbasis ADDIE terbukti efektif meningkatkan kecerdasan emosional siswa sekolah dasar berbasis Islam.